Experimental investigation of in-plane shear behaviour of grey clay brick masonry panels strengthened with SRG. (1st May 2018) - Wang, Xuan; Lam, Chi Chiu; Iu, Vai Pan
Highlights: Diagonal compression tests are carried out on two unreinforced and six SRG strengthened GCB masonry panels with different reinforcement configurations. The strengthening efficiency of SRG system is investigated by comparing global shear stiffness, strength, ductility, and failure mechanisms of tested panels. An analytical investigation and critical discussion are also given. Abstract: Textile reinforced mortar (TRM) composites have received much attention as they are a superior sustainable material and physically compatible with masonry and historical structures. Among the numerous materials used in TRM composites, steel reinforced grout (SRG) which is produced with high strength steel cords embedded in a cementitious mortar matrix, demonstrates exceptional mechanical performance at a relatively low cost. In this paper, an experimental investigation is carried out on their use as in-plane shear reinforcement of masonry wall panels. The masonry panels are constructed with grey clay bricks (GCBs), a unique construction material widely used in traditional Chinese architecture. Diagonal compression tests are carried out on two unreinforced panels and six strengthened panels with different reinforcement configurations. The contribution of the SRG system to strengthening is assessed by examining the shear stiffness, shear strength, ductility under shear, and changes in failure mechanisms. A comparative analysis is carried out by using results from the previous literature, and the analytical methodologies and the practical use of the SRG system are also discussed.